2006
DOI: 10.1191/0269215506cr917oa
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Barthel Index and the Functional Independence Measure during early inpatient rehabilitation after single incident brain injury

Abstract: All measures were appropriate for younger (less than 65 years of age) patients undergoing early inpatient rehabilitation after single incident vascular or traumatic brain injury. The Barthel Index and the total and physical FIM scores showed similar responsiveness, whilst the cognitive FIM score was least responsive. These findings suggest that none of the FIM scores have any advantage over the Barthel Index in evaluating change in these circumstances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
59
1
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 20 publications
2
59
1
3
Order By: Relevance
“…In addition to measuring disability the capacity to capture clinically significant changes in the outcome measured is important (Houlden, Edwards, McNeil, & Greenwood, 2006). This enables a valid measurement of case-mix pretreatment and subsequently the…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition to measuring disability the capacity to capture clinically significant changes in the outcome measured is important (Houlden, Edwards, McNeil, & Greenwood, 2006). This enables a valid measurement of case-mix pretreatment and subsequently the…”
Section: Introductionmentioning
confidence: 99%
“…effectiveness of treatment [12]. In terms of ABI/TBI, measurement must not only involve functional independence, physical impairments, but also a measure of the limitations caused by the cognitive and behavioral impairments which impact independence, especially in community re-entry [12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…20 They are accepted as functional-level assessment tools evaluating the functional status of patients throughout the rehabilitation process. The FIM comprises 18 items, 18 and Linacre et al 21 found that these items define 2 statistically and clinically different indicators: (1) FIM-motor, which assesses disability in motor functions (13 items); and (2) FIM-cognitive, which assesses disability in cognitive functions (5 items).…”
Section: Bi and The Fimmentioning
confidence: 99%